The Role and Perceptions of Teaching Assistants (TAs) in Primary Schools of Azerbaijan - Aliyeva, Yuliya (ADA University, 2022)
Employees are integral and key part of any organization the success of which highly depends on their contributions and performance. The essential role of a leader is to increase productivity of employees considering their needs and stimulating their performance accordingly. However, there are no empirical studies concerning job satisfaction among teaching assistants (TAs) of Azerbaijan. The main aim of this study was to explore the perceptions of TAs in primary schools of Baku and the factors affecting their job satisfaction by means of their experiences, perceptions regarding their role responsibilities, and work relationships with teachers. The collected data was analyzed in relation to Herzberg’s Two-Factor theory (1959) to find out the effect of Hygiene and Motivator factors on motivation and satisfaction of primary school TAs. Semi-structured interviews with nine TAs were conducted to collect data for the study. The given data was coded and grouped into themes under the research questions. The results of the study revealed that the TAs were not well pleased with some hygiene factors such as salary, working conditions and organizational policies and considered them as the source of job dissatisfaction. Motivators were the key contributors to the professional development and growth of TAs as employees and included such factor as work itself. Interestingly, some identified factors, in particular, relationships with peers and administration were contributing to satisfaction while recognition and promotion were mentioned as sources of dissatisfaction. The study revealed the dependency between Motivators and Hygiene factors within Herzberg’s Two-Factor Theory (1959): if the work relationships between TAs and mainstream teachers are positive and effective, it raises the level of inclusion and involvement at the workplace and increases TAs’ job satisfaction.
Keywords: Teaching assistants.; Schools, Primary.; Herzberg’s Two-Factor theory.; Education